Method for preparing functional humus by using nano-iron composite catalyst to induce directional humification of straw and application thereof

CN122627852BActive Publication Date: 2026-10-09INNER MONGOLIA AUTONOMOUS REGION ACAD OF AGRI & ANIMAL HUSBANDRY SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611114565.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-09
Estimated Expiration
2046-07-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有技术存在的上述问题,提供一种纳米铁复合催化剂诱导秸秆定向腐殖化制备功能腐殖质的方法及应用,解决传统无催化水热腐殖化周期长、产率低,单一Fe3+离子催化效率不足、难以满足千万吨级秸秆规模化处置需求的问题;现有腐殖化反应路径不可控,无法定向富集酸性含氧、含氮功能官能团,产品功能单一同质化的技术难题;单一铁催化腐殖质芳香度低、结构稳定性差,土壤长效培肥能力不足的问题;秸秆腐殖化后固液产物未分质利用、全组分资源化附加值低的问题以及通用腐殖产品与北方盐碱农田、大豆/玉米主栽作物适配性差,土壤改良与作物促生效果不佳的问题

Benefits of technology

1、本发明通过三元纳米铁协同催化,将水热腐殖化反应周期从传统24h、单一铁催化6h压缩至4h,生产效率显著提升;人工腐殖酸产率≥16%,相比单一Fe3+催化提升13.6%以上;秸秆综合利用率从传统不足50%提升至98%以上,可支撑千万吨级秸秆规模化处置需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a method for preparing functional humus by using nano-iron composite catalyst to induce directional humification of straw and application thereof, and belongs to the technical field of agricultural solid waste resource utilization and humus synthesis. The method uses agricultural straw as raw material, improves the reaction activity through alkali pre-dissociation, and then uses ternary nano-iron composite catalyst composed of nano-Fe2O3, zero-valent nano-iron and nano-FeCl3 to perform directional hydrothermal humification, so as to induce directional condensation of straw lignocellulose hydrolysis products and enrich acid-containing oxygen and nitrogen functional groups. After the reaction, solid-liquid separation is performed and differential modification is performed, the solid phase is used to prepare nano-iron-based hydrothermal humic carbon for saline-alkali farmland improvement, and the liquid phase is used to prepare functional humic acid foliar fertilizer for crop growth promotion. The application shortens the reaction period to 4 hours, realizes directional regulation of functional groups and high-value utilization of all components of straw, and realizes synchronous improvement of soil fertility and yield increase of soybeans and corn through a matched regional application process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of agricultural solid waste resource utilization, humus synthesis, soil improvement and crop fertilization. Specifically, it relates to a method and application of a nano-iron composite catalyst to induce the directional humification of straw to prepare functional humus, which is particularly suitable for the high-value disposal of agricultural straw, the improvement of saline-alkali degraded farmland and the improvement of quality and yield of grain and oil crops such as soybeans and corn. Background Technology

[0002] Traditional methods of straw disposal mainly involve burning in the field, indiscriminate dumping, and simple composting. Burning straw produces a large amount of greenhouse gases and particulate matter, causing serious air pollution. Simple composting has problems such as long cycle, large land area, and low humic acid yield. The resource utilization rate of straw is less than 50%, making it difficult to fully realize the resource value of straw.

[0003] Hydrothermal humification technology can simulate the natural humus formation process under closed hydrothermal conditions, converting straw lignocellulose into artificial humus. The product can be directly used for soil improvement and crop fertilization, offering advantages such as short reaction cycle, environmental friendliness, and high resource utilization rate. It is currently the mainstream technology for the high-value utilization of agricultural straw. Existing hydrothermal humification technologies are mainly divided into two categories: non-catalyst systems and iron-catalyst systems. Traditional non-catalyst hydrothermal humification uses corn straw and other materials as raw materials, relying on spontaneous hydrolysis and condensation reactions under hydrothermal conditions to generate humus. The reaction cycle is as long as 24 hours, and the yield of artificial humic acid is only 6.77%, resulting in low production efficiency and failing to support the demand for large-scale straw disposal of tens of millions of tons. Iron-catalyst systems mainly use iron-containing materials as catalysts. 3+ Ion catalysis technology, utilizing Fe 3+Lewis acid catalysis accelerates cellulose hydrolysis and condensation of humic precursors, shortening the reaction cycle to 6 hours and increasing humic acid yield, making it a mainstream catalytic process. For example, CN121974757A discloses a method for preparing functional bio-organic fertilizer based on anaerobic fermentation residue from kitchen waste, including the following steps: mixing anaerobic fermentation residue from kitchen waste, straw, catalyst, and water, conducting a hydrothermal reaction, separating solid and liquid to obtain solid residue and hydrothermal liquid; drying, crushing, and sieving the solid residue to obtain biochar; immersing zeolite in the hydrothermal liquid for adsorption to obtain nutrient-loaded zeolite. The catalyst is ferric chloride or magnesium chloride, solving the problems of low resource utilization rate of kitchen waste and the potential threat of biogas residue to soil, achieving efficient soil improvement and crop growth promotion. CN118562149A discloses a preparation system for biomass-based artificial humic acid, first extracting biomass powder using a toluene-ethanol mixed reagent system to obtain purified biomass powder. The prepared purified biomass powder was then transferred to a co-solvent system consisting of water and γ-valerol, and a metal salt catalyst, which can be at least one of copper chloride, ferric chloride, aluminum chloride, zinc chloride, or cobalt chloride, was added to completely liquefy the biomass powder, yielding a biomass-based organic liquid. This biomass-based organic liquid was then transferred to a high-temperature, high-pressure reactor, where an alkaline reagent was added for hydrothermal humification, resulting in a hydrothermal biomass-based organic liquid. Finally, the hydrothermal process was acidified, centrifuged, washed, and freeze-dried to obtain powdered biomass-based artificial humic acid. This method solves the problems of resource consumption and low yield in traditional humic acid preparation methods, achieving efficient and environmentally friendly biomass resource conversion and improved redox performance. CN116606450A discloses a method for promoting the humification of biomass to synthesize artificial humic substances using iron ion catalysis. The method involves crushing the biomass, transferring the crushed biomass to a reaction vessel, adding alkali, an iron ion catalyst, and water, stirring thoroughly, and then conducting a closed hydrothermal reaction. The iron ion catalyst is one or a mixture of ferric chloride, ferric sulfate, and ferric nitrate. The products after the hydrothermal reaction are subjected to solid-liquid separation, and the solid and liquid products are then recovered as humic substances. Solid humic acid is used to remove lead ions from lead-containing wastewater. In the biomass hydrothermal process, using iron ions as a catalyst accelerates the hydrolysis of biomass macromolecules, promotes the conversion of humic substances, and significantly shortens the reaction time. However, existing iron-catalyzed hydrothermal humification technology still has several shortcomings, hindering its industrial application: First, the catalytic mechanism is singular, and functional groups cannot be directionally regulated: single ionic iron can only accelerate hydrolysis and cannot precisely guide the condensation pathway of humic precursors. This makes it difficult to achieve the directional enrichment of acidic oxygen-containing functional groups such as carboxyl and phenolic hydroxyl groups with nitrogen-containing functional groups, resulting in homogeneous humic products that cannot be specifically adapted to specific application scenarios such as saline-alkali soil improvement and nitrogen fixation and growth promotion in legumes. Second, the product structure has poor stability: single Fe... 3+The catalytically prepared humic acid generally suffers from problems such as small molecular weight, low degree of aromatization, and high proportion of unstable carbon components. After being applied to the soil, it is easily decomposed and mineralized by microorganisms, making it difficult to achieve long-term soil fertility and carbon sequestration enhancement. Third, the product utilization mode is extensive: after hydrothermal reaction, solid and liquid two-phase products are generated. Existing technologies mostly focus only on liquid-phase humic acid or solid-phase humic char as a single product. The added value of all components of straw has not been fully explored, and the resource utilization rate needs to be improved. Fourth, there is insufficient regional adaptability: farmland in northern my country generally suffers from low organic matter, soil salinization, and lack of available iron / potassium. The main crops, soybeans and corn, are highly sensitive to iron nutrition and root nodule nitrogen fixation capacity. However, existing general-purpose humic products lack targeted functional design, resulting in limited field application effects and difficulty in matching the needs of regional agricultural production.

[0004] Currently, the industry has only conducted research on single iron salts and single types of nano-iron catalysis for straw humification. There are no reports on the use of ternary nano-iron composite catalytic systems for the directional hydrothermal humification of straw. Furthermore, a complete set of technologies covering catalyst preparation, directional humification, product quality modification, and regional field application has not been developed, resulting in a significant technological gap. Summary of the Invention

[0005] The purpose of this invention is to overcome the aforementioned problems in the existing technology and provide a method and application for preparing functional humus by inducing the directional humification of straw using a nano-iron composite catalyst. This solves the problems of long cycle, low yield, and single Fe content in traditional catalytic-free hydrothermal humification. 3+ The problems include: insufficient ion catalysis efficiency, making it difficult to meet the needs of large-scale straw disposal at the level of tens of millions of tons; uncontrollable existing humification reaction pathways, making it impossible to directionally enrich acidic oxygen-containing and nitrogen-containing functional groups, resulting in the technical challenge of homogeneous and single-function products; low aromaticity and poor structural stability of humic substances catalyzed by single iron, leading to insufficient long-term soil fertility; lack of differentiated utilization of solid and liquid products after straw humification, resulting in low added value of all components; and poor compatibility of general-purpose humification products with saline-alkali farmland in northern China and major soybean / corn crops, resulting in poor soil improvement and crop growth promotion effects. In this invention, "directional humification," "directional condensation," and "directional enrichment" refer to the synergistic catalytic effect of ternary iron nanoparticles, which preferentially directs the condensation pathway of straw hydrolysis products toward the formation of acidic oxygen-containing functional groups such as carboxyl and phenolic hydroxyl groups, as well as nitrogen-containing functional groups such as amides. Compared with ordinary single iron catalytic systems, the total acid functional group content of the products is increased, the proportion of nitrogen-containing functional groups is increased, and the aromatization of the humic substances in the products is improved, thus achieving directional regulation of functional group composition and distinguishing it from the random condensation of ordinary humification processes.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing functional humus by inducing the directional humification of straw using a nano-iron composite catalyst, comprising the following steps: S1. Straw pretreatment: Agricultural straw is air-dried, crushed, and sieved. It is then pre-dissociated using an alkaline solution at 20-30°C. After filtration and draining, the straw moisture content is controlled at 25%-30% to obtain pre-treated straw. Preferably, the air-drying is natural air-drying, and the straw is mechanically crushed and then sieved through a 2mm standard sieve to remove impurities.

[0007] S2. Preparation of ternary nano-iron composite catalyst: Nano Fe2O3, zero-valent nano iron, and nano FeCl3 are mixed in a mass ratio of 5:3:2, lignin activator is added, and ultrasonic dispersion is performed to obtain ternary nano-iron composite catalyst; the particle size of the nano Fe2O3, zero-valent nano iron, and nano FeCl3 is 40~70nm. S3. Directional hydrothermal humification: Pretreated straw, ultrapure water, and ternary nano-iron composite catalyst are added to a hydrothermal reactor, the initial pH of the system is adjusted to 12.5~13.0, and the reaction is carried out at a constant temperature of 170~180℃ for 4 hours to obtain a humified mixture. S4. Solid-liquid separation and differentiated modification: The humic mixture was separated into solid and liquid products by vacuum filtration; the solid product was washed, dried, activated by low-temperature calcination, and compounded with trace elements to obtain nano-iron-based hydrothermal humic char; the liquid product was purified by ultrafiltration, supplemented with glycine, and its physicochemical properties were adjusted to obtain functional humic acid foliar fertilizer.

[0008] Further, the agricultural straw mentioned in S1 is one or more of corn straw, wheat straw, or oat straw; the alkaline solution is a 0.8~1.2 mol / L potassium hydroxide solution, the solid-liquid ratio of straw to alkaline solution is 1 g:10 mL, and the mechanical stirring pre-dissociation time is 1.5 h. The role of alkaline pre-dissociation is to disrupt the crystalline structure of straw cellulose, pre-break the ester bonds between lignin and hemicellulose, loosen the straw fiber structure, reduce the mass transfer resistance of subsequent hydrothermal reactions, and improve the humification reaction rate and product structural stability; at the same time, potassium is introduced to supplement the product with potassium nutrients.

[0009] Further, in S2, the amount of lignin activator added is 2% of the total mass of the ternary nano-iron; the ultrasonic dispersion power is 200W, and the duration is 30min. The lignin activator is a dodecyl dimethyl benzyl ammonium bromide cationic surfactant, which can encapsulate the nano-iron particles through electrostatic adsorption, preventing them from agglomerating in the aqueous phase and improving dispersion stability. The ternary nano-iron composite catalyst produces synergistic catalysis, specifically through the following mechanism: nano-Fe2O3 has abundant surface redox sites, which can adsorb lignin fragments and catalyze their oxidative condensation, improving the aromatization degree and structural stability of humic acid, while simultaneously supplementing the product with long-lasting iron; zero-valent nano-iron has strong reducing activity, which can break the β-1,4 glycosidic bonds of cellulose, enhancing the hydrolysis efficiency of lignocellulose, and simultaneously generating Fe in situ in a hydrothermal alkaline environment. 2+ / Fe 3+ The circulating system continuously exerts its catalytic effect; nano-FeCl3, as a Lewis acid catalyst, can efficiently catalyze the dehydration of monosaccharides to generate humic precursors such as furfural and 5-hydroxymethylfurfural, providing sufficient substrates for subsequent condensation reactions; the three work together to achieve a full-process catalysis of hydrolysis acceleration, precursor directional adsorption, condensation pathway regulation, and structural stabilization, breaking through the performance limitations of single iron catalysts. In addition, lignin activator can improve the dispersibility of nanoparticles in the aqueous phase, avoid aggregation, and give full play to the interfacial catalytic effect of nanomaterials.

[0010] Furthermore, the mass-to-volume ratio of pretreated straw, ultrapure water, and ternary nano-iron composite catalyst in S3 was 1 g:12 mL:0.08 g. The strongly alkaline initial environment promoted lignin dissolution and hydrolysis, matching the optimal reaction conditions for hydrothermal humification.

[0011] Further, the processing steps for the solid products in S4 are as follows: washing three times with ultrapure water, drying at 120℃ to constant weight, and calcining at 300℃ for 1 hour; compounding with medium-quantity elements such as 2.0~3.0 g / kg of available silicon and 2.5~4.0 g / kg of available calcium, the final obtained nano-iron-based hydrothermal humic char has a pH of 7.1~7.2 and a humic acid content ≥190 mg / g. In this step, low-temperature calcination and activation optimizes the pore structure of the humic char, enhancing its adsorption and retention capacity; simultaneously, it converts the loaded iron element into a stable oxide form, allowing for slow release after application to the soil, preventing rapid leaching of iron and achieving long-term iron supply. The compounding of silicon and calcium elements can specifically meet the needs of saline-alkali soil improvement, enhancing soil buffering capacity and structural stability.

[0012] Furthermore, the specific processing steps for the liquid phase product in S4 are as follows: A 1000Da ultrafiltration membrane is used to remove macromolecular impurities, and 0.3~0.7 g / L glycine is added as an organic nitrogen source; the humic acid content in the foliar fertilizer is adjusted to 2.7~2.8 g / L, the iron concentration to 1.1~1.2 g / L, and the pH value to 6.8~7.0. Ultrafiltration purification removes unreacted fiber fragments and macromolecular impurities from the liquid phase, retaining small-molecule active humic acid, which is more conducive to absorption by crop leaves; adding glycine as an organic nitrogen source enhances the nitrogen nutrition and biostimulatory activity of the product. The near-neutral pH is adapted to the tolerance characteristics of crop leaves, avoiding the risk of leaf burn.

[0013] Another objective of this invention is to provide a nano-iron-based hydrothermal humic charcoal, which is neutral, has a humic acid content ≥190mg / g, is loaded with nano-iron oxides, and is compounded with 2.0~3.0g / kg of available silicon and 2.5~4.0g / kg of available calcium as medium-quantity elements of silicon and calcium, which can be used for soil improvement and fertility enhancement in saline-alkali degraded farmland.

[0014] Another objective of this invention is to provide a functional humic acid foliar fertilizer, wherein the functional humic acid foliar fertilizer has a pH of 6.8-7.0, contains 2.7-2.8 g / L humic acid and 1.1-1.2 g / L chelated iron, and is rich in indoleacetic acid and salicylic acid-like plant endogenous hormone analogs, and can be used for foliar spraying of crops such as soybeans and corn to promote growth and improve quality.

[0015] Another objective of this invention is to provide an application of nano-iron-based hydrothermal humic charcoal or functional humic acid foliar fertilizer, in which nano-iron-based hydrothermal humic charcoal is applied as a soil conditioner to saline-alkali degraded farmland, or functional humic acid foliar fertilizer is sprayed onto soybean or corn plants.

[0016] Furthermore, the application dosage of the nano-iron-based hydrothermal humic charcoal is 1-5 g / kg dry soil; it should be evenly incorporated into the soil before sowing and during land preparation, and applied only once during the entire crop growth period; the application dosage should not exceed 5 g / kg to avoid the risk of secondary soil salinization; the functional humic acid foliar fertilizer should be diluted 20 times before use; it should be sprayed continuously from any time point during the crop seedling stage (V3-V5), once every 2 days, for a total of 6 sprays; the spraying time is 8:00-9:00 daily, the spraying amount per plant is 5 mL, and the leaves should be kept moist for no less than 12 hours to improve nutrient absorption efficiency.

[0017] This invention addresses the needs of straw resource utilization and agricultural production by developing a ternary nano-iron directional catalytic humification process. This process enables high-value utilization of all components of straw and customization of product functions, offering the following significant advantages compared to existing technologies: 1. This invention utilizes ternary nano-iron synergistic catalysis to reduce the hydrothermal humification reaction cycle from the traditional 24 hours and 6 hours with single iron catalysis to 4 hours, significantly improving production efficiency; the yield of artificial humic acid is ≥16%, compared to single Fe. 3+ The catalytic efficiency is increased by more than 13.6%; the comprehensive utilization rate of straw has increased from less than 50% in the past to more than 98%, which can support the demand for large-scale straw disposal of tens of millions of tons.

[0018] 2. Achieving targeted regulation of functional groups and customized product functions: This invention utilizes the interfacial adsorption and targeted catalytic effect of nanomaterials to guide the condensation of humic precursors along a preset path, achieving targeted enrichment of acidic oxygen-containing and nitrogen-containing functional groups. The total acid functional group content of the product is ≥7.0mmol / g, and the proportion of nitrogen-containing functional groups is increased by 20%. This breaks through the limitations of traditional product function homogeneity and can be specifically adapted to specific scenarios such as saline-alkali soil improvement and nitrogen fixation and growth promotion of leguminous crops.

[0019] 3. Improved product structural stability and significant long-term fertilization effect: This invention utilizes ternary nano-iron to synergistically regulate the condensation degree of humic acid, enhancing the aromaticity of the product and significantly reducing the proportion of unstable carbon components. The solid-phase humic char is loaded with stable iron oxides, allowing for slow nutrient release upon soil application while simultaneously retaining soil organic carbon. This results in a long-term fertilization capacity that is over 40% higher than that of single iron-catalyzed products. Furthermore, it pioneers a differentiated solid-liquid product modification process: solid-phase preparation of neutral nano-iron-based hydrothermal humic char, primarily for soil salinity improvement and long-term fertilization; and liquid-phase preparation of near-neutral functional humic acid foliar fertilizer, primarily for crop foliar absorption and rapid growth promotion. These two product types complement each other, achieving 100% high-value utilization of all components of straw, significantly increasing the added value per ton of straw product.

[0020] 4. Addressing the specific characteristics of northern farmland, including salinization, iron / potassium deficiency, and the predominantly soybean / corn cultivation areas, this product features targeted functional design: The neutral humic charcoal, rich in organic carbon and silicon-calcium elements, buffers soil salinity and improves soil fertility; the foliar fertilizer, rich in chelated iron and hormone-like substances, enhances soybean photosynthetic efficiency and root nodule nitrogen fixation. When used in conjunction with regionalized application techniques, it can increase soil available phosphorus, readily available potassium, and available iron, leading to increased soybean yield. Simultaneously, it can replace 15%–20% of chemical fertilizers, reducing agricultural non-point source pollution, resulting in significant economic, environmental, and social benefits. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the meaning consistent with their meaning in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein. The reagents used herein may be commercially available related products, and performance testing standards refer to industry or national standards.

[0023] Those skilled in the art will understand that, unless specifically stated otherwise, the singular forms “a,” “an,” “the,” and “the” used herein may also include the plural forms. It should be further understood that the term “comprising” as used in this specification means the presence of the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. The term “and / or” as used herein includes all or any units and all combinations of one or more associated listed items.

[0024] In this invention, the humic acid yield is determined according to GB / T 34766-2017, "Determination of Total Humic Acid Content from Mineral Sources," using the potassium dichromate titration method; the total acid functional group content is determined by potentiometric titration; and the aromaticity is expressed as SUVA. 254 Characterization was performed using absorbance per unit of organic carbon at 254 nm; soil physicochemical indicators were determined using conventional soil agrochemical analysis methods; crop growth and yield indicators were determined using conventional field measurement methods.

[0025] Example 1 This embodiment uses corn stalks as raw material to prepare functional humus. The specific steps are as follows: S1 Straw Pretreatment: Take local corn stalks from Inner Mongolia, air dry them naturally, then crush them with a pulverizer and pass them through a 2mm standard sieve to remove impurities; prepare a 1.0mol / L potassium hydroxide solution, add the straw powder at a solid-liquid ratio of 1g:10mL, and mechanically stir at room temperature (20-30℃) for 1.5h for pre-dissociation; vacuum filter and drain, controlling the straw moisture content to 28%, to obtain pretreated straw.

[0026] Preparation of S2 ternary nano-iron composite catalyst: Nano-Fe2O3, zero-valent nano-iron, and nano-FeCl3 with a particle size of 50nm were mixed evenly in a mass ratio of 5:3:2; dodecyl dimethyl benzyl ammonium bromide accounting for 2% of the total mass of ternary nano-iron was added, and an appropriate amount of ultrapure water was added for dispersion. The mixture was ultrasonically treated at 200W power for 30min to obtain a composite catalyst suspension.

[0027] S3 Directional Hydrothermal Humicization: Pretreated straw, ultrapure water, and ternary nano-iron composite catalyst were added to a polytetrafluoroethylene-lined hydrothermal reactor at a mass-volume ratio of 1g:12mL:0.08g; the initial pH of the system was adjusted to 12.8 with KOH solution, and the reactor was sealed and placed in a heating furnace, heated to 175℃ and reacted at a constant temperature for 4 hours; after the reaction was completed, the reactor was naturally cooled to room temperature to obtain a humified mixture.

[0028] S4 Solid-Liquid Separation and Differential Modification: The humic mixture was vacuum filtered to collect the solid product; it was washed three times with ultrapure water until the filtrate was neutral, and then dried in a 120℃ oven to constant weight; it was then transferred to a muffle furnace for low-temperature calcination and activation at 300℃ for 1 hour, cooled, and then mixed with silicon and calcium in proportion (available silicon 2.5 g / kg, available calcium 3.2 g / kg), ground and mixed to obtain nano-iron-based hydrothermal humic char. The liquid product obtained from vacuum filtration was collected and purified by ultrafiltration using a 1000 Da ultrafiltration membrane to remove macromolecular impurities; 0.5 g / L glycine was added as an organic nitrogen source, and the pH was adjusted to 6.9 to obtain functional humic acid foliar fertilizer.

[0029] Example 2 This embodiment uses wheat straw as raw material, and the process parameters are the same as in Example 1. The specific steps are as follows: S1 Straw pretreatment: Take local wheat straw from Inner Mongolia, air-dry and crush it through a 2mm sieve; use 1.0mol / L potassium hydroxide solution at a solid-liquid ratio of 1g:10mL, stir at room temperature for 1.5h to pre-dissociate, filter and drain, and control the moisture content to 25% to obtain pretreated straw. S2 Preparation of ternary nano-iron composite catalyst: Same as in Example 1. S3 Directional hydrothermal humification: Except for the initial pH of 12.5, other parameters and processes are the same as in Example 1. After reaction, cool to obtain humification mixture. S4 Solid-liquid separation and differentiated modification: The process parameters are the same as in Example 1, and nano-iron-based hydrothermal humic char and functional humic acid foliar fertilizer are prepared respectively.

[0030] Example 3 This experiment uses corn stalks as raw material to prepare functional humus. The specific steps are as follows: S1 Straw Pretreatment: Take local corn stalks from Inner Mongolia, air dry them naturally, then crush them with a pulverizer and pass them through a 2mm standard sieve to remove impurities; prepare a 1.2mol / L potassium hydroxide solution, add the straw powder at a solid-liquid ratio of 1g:10mL, and mechanically stir at room temperature (20-25℃) for 1.5h for pre-dissociation; vacuum filter and drain, controlling the straw moisture content to 30%, to obtain pretreated straw.

[0031] Preparation of S2 ternary nano-iron composite catalyst: Nano-Fe2O3, zero-valent nano-iron, and nano-FeCl3 with particle sizes of 40nm~70nm were mixed evenly in a mass ratio of 5:3:2; lignin activator dodecyl dimethyl benzyl ammonium bromide accounting for 2% of the total mass of ternary nano-iron was added, and an appropriate amount of ultrapure water was added for dispersion. The mixture was ultrasonically treated at 200W power for 30min to obtain a composite catalyst suspension.

[0032] S3 Directional Hydrothermal Humicization: Pretreated straw, ultrapure water, and ternary nano-iron composite catalyst were added to a polytetrafluoroethylene-lined hydrothermal reactor at a mass-volume ratio of 1g:12mL:0.08g; the initial pH of the system was adjusted to 13 with KOH solution, and the reactor was sealed and placed in a heating furnace, heated to 180℃ and reacted at a constant temperature for 4 hours; after the reaction was completed, the reactor was naturally cooled to room temperature to obtain a humified mixture.

[0033] S4 Solid-Liquid Separation and Differential Modification: The humic mixture was vacuum filtered to collect the solid product; it was washed three times with ultrapure water until the filtrate was neutral, and then dried in a 120℃ oven to constant weight; it was then transferred to a muffle furnace for low-temperature calcination and activation at 300℃ for 1 hour, cooled, and then mixed with silicon and calcium in proportion (available silicon 2.5 g / kg, available calcium 3.2 g / kg), ground and mixed to obtain nano-iron-based hydrothermal humic char. The liquid product obtained from vacuum filtration was collected and purified by ultrafiltration using a 1000 Da ultrafiltration membrane to remove macromolecular impurities; 0.5 g / L glycine was added as an organic nitrogen source, and the pH was adjusted to 7 to obtain functional humic acid foliar fertilizer.

[0034] Example 4 This embodiment uses the same raw materials as Example 1. The only difference is that the particle size of the raw materials nano Fe2O3, zero-valent nano iron, and nano FeCl3 used in the preparation of the ternary nano iron composite catalyst is 40 nm. The other process parameters are the same as in Example 1.

[0035] Example 5 This embodiment uses the same raw materials as Example 1. The only difference is that the particle size of the raw materials nano Fe2O3, zero-valent nano iron, and nano FeCl3 used in the preparation of the ternary nano iron composite catalyst is 60 nm. The other process parameters are the same as in Example 1.

[0036] Example 6 This embodiment uses the same raw materials as Example 1. The only difference is that the particle size of the raw materials nano Fe2O3, zero-valent nano iron, and nano FeCl3 used in the preparation of the ternary nano iron composite catalyst is 70 nm. The other process parameters are the same as in Example 1.

[0037] Comparative Example 1-1 This comparative example uses traditional non-catalytic hydrothermal humification. The raw material is the same corn stalks as in Example 1. After natural air drying, the stalks are crushed using a pulverizer and passed through a 2mm standard sieve to remove impurities. The moisture content of the stalks is controlled at 28% to obtain pretreated stalks. The pretreated stalks and ultrapure water are added to a polytetrafluoroethylene-lined hydrothermal reactor at a mass-to-volume ratio of 1g:12mL. The initial pH of the system is adjusted to 12.8 with KOH solution. After sealing, the reactor is placed in a heating furnace and heated to 175℃ for 24 hours. After the reaction, the reactor is allowed to cool naturally to room temperature to obtain a humification mixture. The humification mixture is vacuum filtered to collect the solid product. The solid product is washed three times with ultrapure water until the filtrate is neutral and dried in a 120℃ oven to constant weight. The solid product is then transferred to a muffle furnace and calcined at 300℃ for 1 hour. After cooling, silicon and calcium (2.5g / kg available silicon and 3.2g / kg available calcium) are compounded in proportion, ground, and mixed to obtain nano-iron-based hydrothermal humified carbon. The liquid phase product obtained by vacuum filtration was collected and purified by ultrafiltration using a 1000Da ultrafiltration membrane to remove macromolecular impurities; 0.5 g / L glycine was added as an organic nitrogen source and the pH was adjusted to 6.9 to obtain functional humic acid foliar fertilizer.

[0038] Comparative Examples 1-2 This comparative example is a traditional non-catalyst hydrothermal humification process. The only difference between this example and Comparative Example 1-1 is that the temperature was raised to 175°C and kept constant for 4 hours in a hydrothermal reactor.

[0039] Comparative Example 2 This comparative example uses a single Fe. 3+ Ion-catalyzed hydrothermal humification was carried out using the same raw materials and pretreatment as in Example 1. The difference was that the catalyst in S2 was only ionic FeCl3, and the amount added was the same as the total iron content in Example 1. In S3, the initial pH of the system was adjusted to 12.8, and the reaction was carried out at a constant temperature of 175°C for 6 hours. Other processes were the same as in Example 1.

[0040] Comparative Example 3 This comparative example uses a single nano-Fe2O3 catalyst, with the same amount added as the total iron content in Example 1, and the other process parameters are the same as in Example 1.

[0041] Comparative Example 4 This comparative example uses a single zero-valent nano-iron catalyst. The only difference from Example 1 is that the catalyst in S2 is only zero-valent nano-iron, and the amount added is the same as the total iron content in Example 1. The other process parameters are the same as in Example 1.

[0042] Comparative Example 5 The only difference between this comparative example and Example 1 is that in S1, the corn stalks are directly used for hydrothermal reaction after being crushed and sieved, without undergoing a potassium hydroxide solution pre-dissociation step. The other process parameters are the same as in Example 1.

[0043] Comparative Example 6-1 This comparative example uses a conventional single iron catalytic process. The only difference from Example 1 is that the catalyst used is analytical grade ferric chloride (non-nanoscale), no alkali pre-dissociation is performed, the hydrothermal reaction time is 6 hours, and the other process parameters are the same as in Example 1.

[0044] Comparative Example 6-2 This comparative example uses a conventional single iron catalytic process, and the only difference from Example 1 is that the catalyst used is analytical grade ferric chloride (non-nanoscale), and the hydrothermal reaction time is 6 hours.

[0045] Comparative Example 6-3 This comparative example uses a conventional single iron catalytic process, and the only difference from Example 1 is that the catalyst used is analytical grade ferric chloride (non-nanoscale), and no alkali pre-dissociation is performed.

[0046] Comparative Example 7-1 This comparative example uses a binary nano-iron composite catalyst made of nano-Fe2O3 with a particle size of 50nm and zero-valent nano-iron mixed in a mass ratio of 5:3. The total amount of iron added is exactly the same as in Example 1, and the other process parameters are the same as in Example 1.

[0047] Comparative Example 7-2 This comparative example uses a binary nano-iron composite catalyst made of nano-Fe2O3 and nano-FeCl3 with a particle size of 50nm mixed in a mass ratio of 5:2. The total iron addition is exactly the same as in Example 1, and the other process parameters are the same as in Example 1.

[0048] Comparative Example 7-3 This comparative example uses a binary nano-iron composite catalyst made of zero-valent nano-iron and nano-FeCl3 mixed in a mass ratio of 3:2, with a particle size of 50nm. The total iron addition is exactly the same as in Example 1, and the other process parameters are the same as in Example 1.

[0049] The products of each example and comparative example were tested, and the results are shown in Table 1. Table 1 shows that the humic acid yields of Examples 1-3 all reached over 16%. Specifically, Example 1 achieved a liquid-phase humic acid yield of 16.82%, a 194.1% increase compared to the 5.72% of Comparative Examples 1-2 (calculated as the difference in humic acid yield between the examples and the comparative examples / the humic acid yield of the comparative examples); Example 2 achieved a liquid-phase humic acid yield of 16.15%, a 182.3% increase compared to Comparative Examples 1-2; and Example 3 achieved a liquid-phase humic acid yield of 16.03%. Compared to Comparative Examples 1-2, which showed a 180.2% yield increase, all three examples achieved yield increases of over 180%. Calculated using Example 1 and Comparative Example 6-2 (12.91%), the yield increase was 30.3%; Example 2 and Comparative Example 6-2, the yield increase was 25.1%; and Example 3 and Comparative Example 6-2, the yield increase was 24.2%. All three examples showed yield increases of over 24% compared to the conventional 6-hour reaction of Comparative Example 6-2. Furthermore, the reaction time of this invention was significantly reduced from 6 hours to 4 hours, resulting in a significant improvement in production efficiency per unit time. The total acid functional group content of the products in all examples was ≥7.0 mmol / g, and SUVA... 254 The results were significantly higher than those of the comparative examples, indicating that the ternary nano-iron catalysis achieved the directional enrichment of acidic oxygen-containing functional groups, while simultaneously improving the aromatization degree and structural stability of the product. Comparative Examples 2-4 used single-component nano-iron catalysis, and all indicators were significantly lower than those of Example 1, verifying that nano-Fe2O3, zero-valent nano-iron, and nano-FeCl3 have a synergistic catalytic effect, jointly achieving the entire process of hydrolysis acceleration, precursor directional adsorption, condensation path regulation, and structural stabilization. Comparative Example 5 did not undergo alkali pre-dissociation, resulting in a decrease in product performance, indicating that alkali pre-dissociation can loosen the straw fiber structure and pre-break the lignin-hemicellulose chemical bonds, effectively improving the reaction efficiency of subsequent hydrothermal humification. Furthermore, Examples 4-6 show that within the entire particle size range of 40-70 nm, ternary nano-iron catalysts of different particle sizes can stably achieve a humic acid yield of approximately 16%, with a total acid functional group content ≥7.0 mmol / g, indicating that there is no substantial difference in catalytic effect within this particle size range.

[0050] Table 1. Performance test results of products from each embodiment and comparative example.

[0051] The core indicators of the liquid foliar fertilizers of Example 1 and Comparative Example 6 were measured, and the results are shown in Table 2: Table 2 Comparison of key indicators of functional humic acid foliar fertilizer

[0052] As can be seen from Table 2, the functional humic acid foliar fertilizer prepared by this invention has a higher content of humic acid and available iron, and is rich in indoleacetic acid and salicylic acid analogues of plant endogenous hormones. Its biostimulatory activity is significantly better than that of conventional single iron catalytic products, and it is more suitable for the needs of crop foliar growth promotion.

[0053] The tested soil was saline-alkali farmland soil from the Songnen Plain in Northeast China, with the following basic properties: pH 8.62, organic matter 12.37 g / kg, available phosphorus 8.24 mg / kg, available potassium 96.35 mg / kg, and available iron 4.21 mg / kg. Pot experiments were conducted with 5 kg of dry soil per pot, and 3 g / kg of dry soil was applied with humic acid. A blank control group (without humic acid) was included. Each treatment was replicated three times. Soil physicochemical properties were measured after 30 days of constant temperature incubation, and the results are shown in Table 3. Table 3 Comparison of Soil Improvement Effects

[0054] Table 3 shows that applying the nano-iron-based hydrothermal humic char of this invention can significantly buffer the pH of saline-alkali soils, while greatly increasing the content of soil organic matter, available phosphorus, available potassium, and available iron. Specifically, soil organic matter increased by 50.5%, and available iron increased by 107.4%, demonstrating a significantly better improvement effect than conventional single-iron catalytic humic char, thus meeting the improvement needs of saline-alkali degraded farmland in northern China. Further verification of the humic char application dosage in Example 1 was conducted using a low dosage of 1 g / kg dry soil and a high dosage of 5 g / kg dry soil. All other cultivation conditions were identical to the previous pot experiment on soil improvement. The experiment showed that after 30 days of cultivation at the low dosage of 1 g / kg dry soil, the soil pH decreased to 8.37, organic matter increased to 15.24 g / kg, and available iron increased to 6.18 mg / kg, achieving a basic improvement effect on mildly saline-alkali soils without the risk of secondary salinization. After 30 days of cultivation with a high dose of humic char (5 g / kg dry soil), the soil pH decreased to 7.88, organic matter increased to 20.17 g / kg, available iron increased to 9.24 mg / kg, and there was no obvious salt accumulation, nor did it cause salinization. It is suitable for the improvement needs of severely saline-alkali farmland.

[0055] A soybean pot experiment was conducted using the variety "Dongnong 52". Foliar fertilizer was applied starting at the V3 stage. A blank control group (sprayed with water), a comparative control group (foliar fertilizer group 6), and a foliar fertilizer group (Example 1) were set up, with each treatment replicated three times. Spraying method: The stock solution was diluted 20 times and sprayed once every two days for a total of six sprays; spraying was done daily from 8:00 to 9:00 AM, with a single-plant application rate of 5 mL. Plant height, aboveground fresh weight, and root nodule nitrogenase activity were measured at full bloom. The number of pods per plant and yield were measured at maturity. The results are shown in Table 4. Table 4 Comparison of Soybean Growth and Yield Indicators

[0056] Table 4 shows that spraying the functional humic acid foliar fertilizer of this invention can significantly promote soybean growth, increase nitrogenase activity in root nodules and yield; compared with the blank control, the yield per plant increased by 43.2%; compared with conventional iron-catalyzed foliar fertilizer, the yield increased by 22.2% and the nitrogenase activity in root nodules increased by 38.9%, verifying the excellent effect of the product in promoting growth and improving quality of leguminous crops. It can efficiently supplement iron nutrition in soybeans, improve photosynthetic efficiency and nitrogen fixation capacity in root nodules, significantly improve quality and increase yield, and its effect is better than that of commercially available conventional iron fertilizers.

[0057] Further verification was conducted by spraying the functional humic acid foliar fertilizer from Example 1 of this invention starting at soybean V4 stage, with all other spraying conditions being completely consistent with the previous soybean pot experiment. At full bloom, the soybean plant height was measured to be 41.5 cm, the above-ground fresh weight was 28.74 g / plant, the root nodule nitrogenase activity was 7.58 μmol C2H4 / (g·h), and the yield per plant at maturity could reach 11.82 g. The growth-promoting and yield-increasing effects were not significantly different from those of spraying at V3 stage.

[0058] The functional humic acid foliar fertilizer of this invention was sprayed starting from soybean V5 stage. The other spraying conditions were completely consistent with the previous soybean pot experiment. The soybean plant height was 40.8 cm at full flowering stage, the above-ground fresh weight was 27.61 g / plant, the root nodule nitrogenase activity was 7.24 μmol C2H4 / (g·h), and the yield per plant at maturity could reach 11.71 g, which can still achieve a stable effect of promoting growth and improving quality.

[0059] A pot experiment was conducted using the maize variety "Zhengdan 958" and the saline-alkali farmland soil from the Songnen Plain in Northeast China (mentioned above). The nano-iron-based hydrothermal humic char prepared in Example 1 of this invention was applied to the soil at a rate of 3 g / kg dry soil. After 30 days of cultivation, the soil pH was measured to have decreased to 7.97, the organic matter content increased to 18.31 g / kg, and the available phosphorus, available potassium, and available iron were all significantly increased. The functional humic acid foliar fertilizer of this invention was sprayed starting from the V3 stage of maize, once every 2 days, for a total of 6 sprays. At maturity, the maize plant height was measured to be 27% higher than the blank control, and the yield per plant was 32% higher, which also confirmed the applicability and stable effect on maize crops.

[0060] The test results from the above embodiments and comparative experiments show that the ternary nano-iron directional catalytic humification process of the present invention can efficiently realize the resource utilization of straw. The two types of products prepared are suitable for the soil and crop needs of northern regions and have excellent application effects and industrialization prospects.

[0061] The preferred embodiments of the present invention have been described in detail above, and are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing functional humus by inducing the directional humification of straw using a nano-iron composite catalyst, characterized in that, Includes the following steps: S1. Straw pretreatment: Agricultural straw is air-dried, crushed, and sieved. It is then pre-dissociated using a potassium hydroxide alkaline solution at 20-30℃. After filtration and draining, the straw moisture content is controlled at 25%-30% to obtain pre-treated straw. The agricultural straw is one or more of corn straw, wheat straw, or oat straw. The alkaline solution is a 0.8-1.2 mol / L potassium hydroxide solution, and the solid-liquid ratio of straw to alkaline solution is 1 g: 10 mL. S2. Preparation of ternary nano-iron composite catalyst: Nano-Fe2O3, zero-valent nano-iron, and nano-FeCl3 were mixed in a mass ratio of 5:3:2, a lignin activator was added, and the mixture was ultrasonically dispersed to obtain a composite catalyst; the particle size of the nano-Fe2O3, zero-valent nano-iron, and nano-FeCl3 was 40~70nm; the lignin activator was a dodecyl dimethyl benzyl ammonium bromide cationic surfactant; the amount of lignin activator added was 2% of the total mass of the ternary nano-iron; S3. Directed hydrothermal humification: Pretreated straw, ultrapure water, and ternary nano-iron composite catalyst were added to a hydrothermal reactor, the initial pH of the system was adjusted to 12.5~13.0, and the reaction was carried out at a constant temperature of 170~180℃ for 4 hours to obtain a humified mixture; the mass-volume ratio of pretreated straw, ultrapure water, and ternary nano-iron composite catalyst was 1g:12mL:0.08g. S4. Solid-liquid separation and differentiated modification: The humic mixture is separated into solid and liquid products by vacuum filtration; Nano-iron-based hydrothermal humic char was prepared by cleaning, drying, low-temperature calcination activation, and compounding with silicon and calcium as medium elements. The liquid-phase product was purified by ultrafiltration, supplemented with glycine, and its physicochemical properties were adjusted to prepare a functional humic acid foliar fertilizer. It was compounded with 2.0–3.0 g / kg of available silicon and 2.5–4.0 g / kg of available calcium as medium elements. 0.3–0.7 g / L of glycine was added as an organic nitrogen source. After adjustment, the humic acid content in the functional humic acid foliar fertilizer was 2.7–2.8 g / L, and the iron concentration was 1.1–1.2 g / L.

2. The method according to claim 1, characterized in that, The mechanical stirring pre-dissociation time is 1.5 hours.

3. The method according to claim 1, characterized in that, The ultrasonic dispersion power is 200W, and the duration is 30min.

4. The method according to claim 1, characterized in that, The specific steps for processing the solid products in S4 are as follows: washing three times with ultrapure water, drying at 120℃ to constant weight, and calcining at 300℃ for 1 hour; the final obtained nano-iron-based hydrothermal humic carbon has a pH of 7.1~7.

2.

5. The method according to claim 1, characterized in that, The specific steps for processing the liquid phase products in S4 are as follows: remove macromolecular impurities using a 1000Da ultrafiltration membrane and adjust the pH value to 6.8~7.

0.

6. A nano-iron-based hydrothermal humic char, characterized in that, The nano-iron-based hydrothermal humic carbon is prepared by any one of claims 1 to 5; the nano-iron-based hydrothermal humic carbon is neutral, loaded with nano-iron oxides, and compounded with 2.0 to 3.0 g / kg of available silicon and 2.5 to 4.0 g / kg of available calcium as medium-quantity elements of silicon and calcium.

7. A functional humic acid foliar fertilizer, characterized in that, The functional humic acid foliar fertilizer is prepared by the method described in any one of claims 1 to 5; the pH of the foliar fertilizer is 6.8 to 7.0, and it contains 2.7 to 2.8 g / L of humic acid and 1.1 to 1.2 g / L of chelated iron.

8. The application of the nano-iron-based hydrothermal humic charcoal of claim 6 or the functional humic acid foliar fertilizer of claim 7, characterized in that, Nano-iron-based hydrothermal humic char can be applied as a soil conditioner to saline-alkali degraded farmland, or functional humic acid foliar fertilizer can be sprayed onto soybean plants.

9. The application according to claim 8, characterized in that, The dosage of the nano-iron-based hydrothermal humic charcoal is 1-5 g / kg dry soil; it should be evenly incorporated into the soil before sowing and applied only once during the entire crop growth period; the functional humic acid foliar fertilizer should be diluted 20 times with the original solution; it should be sprayed continuously from any time point during the V3-V5 seedling stage of the crop, once every 2 days, for a total of 6 sprays; the spraying time is 8:00-9:00 every day, the spraying amount per plant is 5 mL, and the leaves should be kept moist for no less than 12 hours.

Citation Information

Patent Citations

  • Method for synthesizing artificial humus by catalyzing and promoting biomass humification through iron ions and application

    CN116606450A

  • Biomass-based artificial humic acid preparation system and method

    CN118562149A

  • Functional bio-organic fertilizer based on anaerobic fermentation biogas residues of kitchen garbage as well as preparation method and application of functional bio-organic fertilizer

    CN121974757A

  • Method for preparing silicon-containing super mineral source potassium humate by using rice husks and application of silicon-containing super mineral source potassium humate

    CN116462855A

  • Method of promoting rice growth using Artificial Humic Acid Synthesized by Catalysis of Nanoscale Ferric Oxide

    US20240164382A1